2014
DOI: 10.1371/journal.pone.0108400
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Bone Health in Pediatric Patients with Hemolytic Anemia

Abstract: IntroductionSickle cell anemia and thalassemia result in impaired bone health in both adults and youths. Children with other types of chronic hemolytic anemia may also display impaired bone health.Study DesignTo assess bone health in pediatric patients with chronic hemolytic anemia, a cross-sectional study was conducted involving 45 patients with different forms of hemolytic anemia (i.e., 17 homozygous sickle cell disease and 14 hereditary spherocytosis patients). Biochemical, radiographic and anamnestic param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
(21 reference statements)
3
20
1
1
Order By: Relevance
“…Clinical and anamnestic parameters were assessed as previously described in detail ( 24 ). Briefly, a physical examination, including determination of weight, height, and pubertal status was performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and anamnestic parameters were assessed as previously described in detail ( 24 ). Briefly, a physical examination, including determination of weight, height, and pubertal status was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, a physical examination, including determination of weight, height, and pubertal status was performed. Patients were also asked to complete a standardized questionnaire regarding vitamin D, calcium and nutritional supplement intake, screen hours and hours of physical activity per day ( 24 ). In addition, the patients were asked for presence of bone pain in the form of regularly occurring (on more than half of the days in the last month), spontaneous, back pain or exercise related knee pain.…”
Section: Methodsmentioning
confidence: 99%
“…In a heterogeneous group of children with mixed hemolytic anemia diagnoses, the degree of hemolytic disease activity was found to influence bone metabolism, mainly promoting the imbalance in the receptor activator of nuclear factor-kappa B (RANK)/RANK ligand (RANKL)/osteoprotegerin (OPG) system resulting in higher serum RANKL/OPG (sRANKL/OPG) ratio and lowering the bone formation marker, osteocalcin (OC). 11 Lower OC levels were also associated with evidence of hypoparathyroidism in another group of thalassemic children. 12e14 However, this finding was not supported in other studies, 11,15 in which thalassemic children showed significantly higher OC levels compared to controls.…”
Section: Introductionmentioning
confidence: 93%
“…11 Lower OC levels were also associated with evidence of hypoparathyroidism in another group of thalassemic children. 12e14 However, this finding was not supported in other studies, 11,15 in which thalassemic children showed significantly higher OC levels compared to controls.…”
Section: Introductionmentioning
confidence: 93%
“…Several haematological disorders and diseases display an associated osteoporosis phenotype or low bone mineral density. They include patients suffering from beta‐thalassaemia major (Mahachoklertwattana et al , ; Yacobovich & Tamary, ), chronic haemolytic and pernicious anaemia (Gurevitch et al , ; Schundeln et al , ), haemophilia (Barnes et al , ; Iorio et al , ), sickle cell anaemia (Sanner & Ramin, ; Yacobovich & Tamary, ) and bone marrow failure (Townsley et al , ). One could argue that, where a chronic erythropoiesis exists (e.g.…”
Section: The Reciprocal Relationship Between Bone and Haematopoiesismentioning
confidence: 99%